2012
DOI: 10.3390/molecules17056033
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of T. violacea Rhizome Extract Against Hypercholesterolemia-Induced Oxidative Stress in Wistar Rats

Abstract: The present study examines the effect of methanolic extract of T. violacea rhizomes on high cholesterol (2%) diet fed rats (HCD). At the end of 4 weeks, serum total protein, albumin, reduced glutathione (GSH), and markers of oxidative stress viz., catalase (CAT), superoxide dismutase (SOD), thiobarbituric acid reactive substances (TBARSa marker of lipid peroxidation), glutathione-S-transferase (GST) and glutathione peroxidase (GPx) in the serum, aorta, liver and heart of HCD and normal rats were assessed and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 42 publications
7
24
1
Order By: Relevance
“…The above hypothesis is further supported by Molinar-Toribio et al [46] who showed that glutathione system was not activated in the hearts of SHROB rats. However, a decrease in GSH has been observed in the hearts of female cholesterol-fed Wistar rats [47].…”
Section: Discussionmentioning
confidence: 98%
“…The above hypothesis is further supported by Molinar-Toribio et al [46] who showed that glutathione system was not activated in the hearts of SHROB rats. However, a decrease in GSH has been observed in the hearts of female cholesterol-fed Wistar rats [47].…”
Section: Discussionmentioning
confidence: 98%
“…Gemfibrozil (GF) (Sigma Aldrich chemicals, Germany) was supplied as white powder, suspended in small amount of tween 80 and distilled water and was given with daily oral gavage at a dose of 100 mg/kg [47].…”
Section: Drugs and Chemicalsmentioning
confidence: 99%
“…The trafficking depends on the activities of hepatic LPL that hydrolyses lipoproteins 13 . in the present study, the significant downregulation of LPL in the sulindac-diclofenac group might indicate elevation of lipoprotein in the blood and 14 have recently reported that hypercholesterolemia increases the level of lipid peroxidation in the liver. Therefore, it could be expected that both sulindac and diclofenac might lead to lethal liver cell injury by lipid peroxidation via down-regulating LPL and hyperlipidemia.…”
Section: Discussionmentioning
confidence: 74%